Distribution of 28 kDa Calbindin-Immunopositive Neurons in the Cat Spinal Cord - Merkulyeva, Natalia; Veshchitskii, Aleksandr; Makarov, Felix; Gerasimenko, Yury; Musienko, Pavel (Frontiers in Neuroanatomy, 2016)
The distribution of vitamin D-dependent calcium-binding protein (28 kDa calbindin) was investigated in cat lumbar and sacral spinal cord segments (L1-S3). We observed specific multi-dimensional distributions over the spinal segments for small immunopositive cells in Rexed laminae II-III and medium-to-large cells of varying morphology in lamina I and laminae V-VIII. The small neurons in laminae II-III were clustered into the columns along the dorsal horn curvature. The medium-to-large cells were grouped into four assemblages that were located in (1) the most lateral region of lamina VII at the L1-L4 level; (2) the laminae IV-V boundary at the L5-L7 level; (3) the lamina VII dorsal border at the L5-L7 level; and (4) the lamina VIII at the L5-S3 level. The data obtained suggest that the morphological and physiological heterogeneity of calbindin immunolabeling cells formed morpho-functional clusters over the gray matter. A significant portion of the lumbosacral enlargement had immunopositive neurons within all Rexed laminae, suggesting an important functional role within and among the spinal networks that control hindlimb movements.